Heart rate Encapsulation and Response Tool using Sentiment Analysis - Prabadevi B.; Nandyala Srujana Reddy; Deepa B. (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Users of every system expect it to get better. Providing feedback to the owners or management was difficult but with the advent of technology, it has become handy. Users can now post their comments through online blogs, android apps and websites. Due to the enormous data piling up every second causes a problem in analyzing it. In this paper, sentiment analysis is used for analyzing comments and reviews for hospital management system are demonstrated with real time data. The tools, algorithms and methodology that could fetch accurate results is described. Experimental results indicate 90% of accuracy in proposed system. The review report generated would help the hospital management to identify the positive and negative feedback which further assists them in improving their facilities that could not only create customer satisfaction but also enhanced business processes.